Experimental evaluation of sound insulation of light steel frame façades that use horizontal inter-stud stiffeners and different lining materials. (December 2015) - Paul, Stephan; Radavelli, Graziella F.; da Silva, Andrey R.
Abstract: Sound insulation of light steel frame (LSF) and wood stud double walls is being studied for several decades. However, some specific cases that include the presence of horizontal stiffeners or the use of specific linings, such as cement boards for the outer lining, instead of materials like OSB-resin panels or vinyl siding, are rarely investigated. Thus ten different LSF walls, using sheatings made from OSB panels, cement boards, plasterboards, Smartside OSB-resin panels, PVC panels and polymer mortar covered XPS panels, and having additional horizontal stiffeners between the LSF studs, were mounted in a sound transmission measurement facility and measurements were carried out in accordance with the ISO 10140:2010 package. Sound insulation was characterized by means of the sound reduction index R, the weighted sound reduction index R w, spectral adaptation terms C ; C tr and sound transmission class. The influence of resilient channels and foam tape, placed between panels and the metallic studs, was also evaluated. Weighted sound reduction indices R w ranged from 43 dB to 47 dB, being the smallest for a wall that uses PVC cladding and the largest for the wall that uses cement board sheating. The addition of resilient channels and foam tape provides an increase of up to 5 dB in R w and STC. The slight increase in sound insulation above the modified mass-air-mass resonance provided by the resilient channels, leveling off at max 10 dB, was predicted correctly by a simple and generic model for the modified mass-air-mass resonance from the literature. Highlights: Sound insulation of LSF facades with several linings, e.g. cement board, measured. LSF walls used vertical studs, horizontal inter-stud stiffeners and resilient channels. Stiffeners and higher panel radiation cancel benefit of full cavity filling. Published model describes modified mass-air-mass resonance for resilient channel use. Max increase in R is 10 dB several octaves above modified mass-air-mass resonance.